Dynamic performance of a multi-story traditional timber pagoda. (15th March 2018) - Wu, Yajie; Song, Xiaobin; Gu, Xianglin; Luo, Lie
Highlights: A one-fifth scaled seven-story traditional timber pagoda was fabricated and tested on a shaking table. Artificial and natural earthquake records of various intensities up to 0.44 g were considered to excite the nonlinear elastic-plastic responses of the pagoda model. Ambient vibration, white noise excitation and inter-story load-drift hysteretic curves were analyzed to identify the dynamic properties of the model and the results from different methods were discussed. Abstract: This paper presents a study on the dynamic performance of a multi-story traditional timber pagoda. A shaking table test was conducted with a 1:5 scaled pagoda model and various excitation intensities. Both artificial and recorded earthquake waves were considered. Ambient excitation test before seismic excitations and white noise excitation tests during the intervals of increasing seismic excitations were conducted to detect the fundamental frequencies and damping ratios of the model pagoda. Equivalent story stiffness was evaluated from the measured inter-story load-displacement hysteretic curves and a lumped mass model was established to determine the dynamic properties of the pagoda during strong excitations. It was found that the pagoda model survived all the input earthquake excitations (up to 0.44g in PGA) with only minor damages. The model frequencies detected after increasing earthquake excitations decreased only by 16% while the damping ratio increased from 1.24% to more than 10%, indicating a good seismic resilience of the pagoda. It was also found that the detected frequencies highly relied on the intensity of the excitations (up to 59% in difference), possibly due to the transition between static and sliding frictions amongst wood members and the recoverable looseness of the mortise-tenon joints.